HUBUNGAN ANTARA HARDINESS DENGAN ACADEMIC BURNOUT SISWA KELAS XI SMA NEGERI 1 KOTA JAMBI PADA MASA PANDEMI COVID-19: THE RELATIONSHIP BETWEEN HARDINESS AND ACADEMIC BURNOUT FOR ELEVENTH GRADE STUDENTS OF STATE SENIOR HIGH SCHOOL 1 JAMBI CITY DURING THE COVID-19 PANDEMIC - M. Ivan Aypi; Yun Nina Ekawati; Jelpa Periantalo (Jurnal Psikologi Jambi, 2022)
Introduction The Covid pandemic-19 has changed the learning system. Where students are required to learn a lot from home which has an impact on student psychology, namely the emergence of burnout. Burnout is characterized by fatigue, cynicism about tasks, and decreased competence. However, students who have hardiness can be committed and able to face the learning system during a pandemic.This study aimed to prove the relationship between hardiness and academic burnout for eleventh grade students of State Senior High School 1 Jambi City during the Covid-19 pandemic. Methods This research was a quantitative research with a correlational approach. The population of this research were eleventh grade students of State Senior High School 1 Jambi city. The research sample was taken using purposive sampling technique with a total of 190 students. Hardiness and academic burnout scales were distributed online by google form application. Data analysis technique was using Pearson correlation. Results The relationship between hardiness and academic burnout for eleventh grade students of State Senior High School 1 Jambi City during the Covid-19 pandemic resulted in a significant negative correlation with an r value of -0.617 and a p value <0.05. Conclusions and Suggestions Hardiness has a negative relationship with academic burnout. Therefore, it is hoped that all parties will be able to overcome academic burnout and increase hardiness in the high school students, especially in State Senior High School 1 Jambi City. Keywords: hardiness, academic burnout, high school students, Covid-19 pandemic. Abstrak Pendahuluan Masa pandemi Covid-19 memberikan perubahan sistem pembelajaran. Dimana siswa lebih dituntut banyak belajar dari rumah yang berdampak pada psikis pelajar, yaitu timbulnya burnout. Burnout ditandai dengan kelelahan, rasa sinis terhadap tugas, serta menurunnya kompetensi. Namun siswa yang memilki hardiness dapat berkomitmen serta mampu menghadapi sistem pembelajaran di masa pandemi. Penelitian ini bertujuan untuk membuktikan adanya hubungan antara hardiness dengan academic burnout siswa kelas XI SMA Negeri 1 Kota Jambi pada masa pandemi Covid-19. Metode Penelitian ini merupakan penelitian kuantitatif dengan pendekatan korelasional. Populasi penelitian ini adalah siswa kelas XI SMA Negeri 1 kota Jambi. Pengambilan sampel penelitian menggunakan teknik purposive sampling dengan total 190 siswa. Skala hardiness dan academic burnout disebarkan secara online melalui google form. Teknik analisis data menggunakan korelasi pearson Hasil Hubungan antara hardiness dengan academic burnout siswa kelas XI SMA Negeri 1 kota Jambi pada masa pandemi Covid-19 menghasilkan korelasi negatif signifikan dengan nilai r sebesar -0,617 serta p value < 0,05. Kesimpulan dan Saran hardiness memiliki hubungan negatif dengan academic burnout. Oleh karena itu, diharapkan kepada semua pihak untuk dapat mengatasi academic burnout dan meningkatkan hardiness pada siswa SMA, khususnya SMA Negeri 1 kota Jambi. Kata Kunci : hardiness, academic burnout, siswa SMA, pandemi Covid-19